Advances in the treatment of lower-extremity ischemia-reperfusion injury - Peng, Jin; Deng, Tang; Wang, Xunkai; Liang, Jinxi; Wu, Jiangpeng; Li, Binglong; Lv, Jun; Wu, Shenmei; Zhong, Shijie; Yao, Chen; Jin, Guiyun (Frontiers in Pharmacology, 2025)
Lower-limb ischemia–reperfusion injury (LL-IRI) is a frequent and serious complication following reperfusion therapy for lower-limb arterial occlusion. It can be caused by trauma, arterial stenosis, thrombotic occlusion, and atherosclerosis. As a prevalent peripheral vascular disease, LL-IRI results in local tissue damage and triggers systemic inflammatory responses that can lead to multiple-organ dysfunction syndrome, as well as multiorgan failure and death in severe cases. Despite its clinical significance, the mechanisms underlying IRI remain poorly understood, and no specific targeted drugs or effective emergency interventions are currently available. Therefore, this review provides a comprehensive analysis of the domestic and international literature published over the past decade regarding the disease definition, pathogenesis, and therapeutic advances in LL-IRI. It summarizes current pharmacological and non-pharmacological interventions, including antioxidant stress management, anti-inflammatory approaches, and oxidative stress reduction strategies. This review aims to advance the exploration of LL-IRI pathogenesis and proposes novel therapeutic perspectives for innovative drug development.